Amber Brown sees red - Danziger, Paula, 1944-2004; Ross, Tony (New York : Scholastic, 1998)
The year that she is in the fourth grade is a difficult one for Amber, as she tries to deal with escalating telephone fights between her divorced parents and her father's impending return to take joint custody of her.
"Little Apple paperback."
680
Accelerated Reader AR
Keywords: Divorce -- Juvenile fiction; Schools -- Juvenile fiction